Clinical spectrum of arthritis in children: A single center study from eastern India - Das E; Roy SM; Pati S; Sinha MK; Datta S; Sarkar S; Sherpa N (Journal of Medical and Scientific Research)
Background: The importance and awareness of pediatric rheumatic diseases (PRDs) are increasing globally. Arthritis in children is a condition that can potentially lead to complications. It can be a manifestation of multiple disease processes. This study was aimed at identifying the common causes and evaluating the clinical profile of pediatric arthritis in Eastern India.